Clinical translation of microfluidic sensor devices: focus on calibration and analytical robustness. Issue 15 (10th July 2019) - Gowers, Sally A. N.; Rogers, Michelle L.; Booth, Marsilea A.; Leong, Chi L.; Samper, Isabelle C.; Phairatana, Tonghathai; Jewell, Sharon L.; Pahl, Clemens; Strong, Anthony J.; Boutelle, Martyn G.
Abstract : Modular platform providing the building blocks to translate specialised microfluidics from the laboratory to a clinical environment. Abstract : We present approaches to facilitate the use of microfluidics outside of the laboratory, in our case within a clinical setting and monitoring from human subjects, where the complexity of microfluidic devices requires high skill and expertise and would otherwise limit translation. Microfluidic devices show great potential for converting complex laboratory protocols into on-chip processes. We demonstrate a flexible microfluidic platform can be coupled to microfluidic biosensors and used in conjunction with clinical microdialysis. The versatility is demonstrated through a series of examples of increasing complexity including analytical processes relevant to a clinical environment such as automatic calibration, standard addition, and more general processes including system optimisation, reagent addition and homogenous enzyme reactions. The precision and control offered by this set-up enables the use of microfluidics by non-experts in clinical settings, increasing uptake and usage in real-world scenarios. We demonstrate how this type of system is helpful in guiding physicians in real-time clinical decision-making.